Universal design : a practical guide to creating and recreating interiors of academic libraries for teaching, learning and research - Staines, Gail M., 1961- (Chandos information professional series., 2012)
Universal Design provides practitioners, graduate students, and other professionals interested in obtaining practical advice on how to effectively create and re-create interiors of academic libraries for teaching, learning, and research. The academic library 'as place' continues to evolve around the idea that the existing environment can have multiple uses. Partnerships with other college and university agencies, such as centers for teaching excellence and writing centers have compatible missions with those of academic libraries. Established within the building-proper these facilities will bet.